Pengaruh Implementasi Strategi IMC terhadap Keputusan Mendaftar Siswa di SMK Telkom Sidoarjo Tahun Ajaran 2022/2023 - Rusli Akhmad Junaedi; Tony S. Soekrani (Fakultas Ilmu Komunikasi UKWMS, 2023)
ABSTRACT The study is to describe and examine the effect of implementing IMC strategy on the decision of student to enrollment at Vocational School of Telkom Sidoarjo during academic year of 2022/2023. The background of which was based on the result of new student enrollment at Vocational School of Telkom Sidoarjo throughout academic year of 2021/2022, during Covid-19 pandemic outbreak to the transition of new normal era, reporting a total of 231 student from the targeted number of 250. The results of new student enrollment at Vocational School of Telkom Sidoarjo during academic year of 2022/2023, however, has exceeded the target by achieving a total of 240 student from the targeted number of 223. The research was conducted using explanatory quantitative method which included 150 respondents. The samples were collected using simple random sampling, while the data was collected through questionnaire. In addition, the data was processed through data validity test consisting validity and reliability test, as well as classical assumption test consisting normality test, multicollinearity test, and heteroscedasticity test. Moreover, the data was analyzed using descriptive statistical analysis and parametric inferential statistics. Furthermore, the hypothesis test was established through multiple linear regression test, partial test (t test), simultaneous test (F test), and coefficient of multiple determination test (R2). The findings suggest that the event & experience variable performed a significant effect with a substantial relationship, while the digital marketing variable represented a significant effect with a substantial relationship on the decision to enrollment at Vocational School of Telkom Sidoarjo. Additionally, the implementation of IMC strategy as measured by variable of advertising, sales promotion, event & experience, public relations, direct marketing, personal selling, and digital marketing simultaneously influenced the decision of student to enrollment at Vocational School of Telkom Sidoarjo. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan dan menguji pengaruh implementasi strategi IMC terhadap keputusan mendaftar siswa di SMK Telkom Sidoarjo pada tahun ajaran 2022/2023. Penelitian ini dilatarbelakangi oleh hasil PPDB SMK Telkom Sidoarjo tahun ajaran 2021/2022 yang bertepatan dengan wabah pandemi Covid-19 melanda hingga transisi era new normal pandemi Covid-19 menunjukan pencapaian sejumlah 231 siswa dari target 250 siswa. Akan tetapi, PPDB SMK Telkom Sidoarjo tahun ajaran 2022/2023 mampu melebihi target dengan pencapaian sebanyak 240 siswa dari target 223 siswa. Metode penelitian yang digunakan adalah kuantitatif eksplanatoris dengan jumlah responden sebanyak 150 responden. Teknik pengambilan sampel dalam penelitian ini adalah simple random sampling. Teknik pengambilan data yang dalam penelitian ini berupa kuisioner. Teknik pengolahan data dalam penelitian ini menggunakan uji keabsahan data yang terdiri dari uji validitas dan uji reliabilitas serta uji asumsi klasik yang terdiri dari uji normalitas, uji multikolinearitas, dan uji heteroskedastisitas. Teknik analisis data dalam penelitian ini adalah analisis statistika deskriptif dan statistik inferensial parametrik. Pengujian hipotesis dalam penelitian ini dilakukan dengan uji regresi linear berganda, uji parsial (uji t), uji simultan (uji F), dan uji koefisien determinasi berganda (R2). Hasil dalam penelitian ini adalah variabel event & experience berpengaruh signifikan dengan hubungan yang cukup dan variabel digital marketing berpengaruh signifikan dengan hubungan yang cukup berarti terhadap keputusan pendaftaran di SMK Telkom Sidoarjo. Implementasi strategi IMC yang diukur dengan variabel advertising, sales promotion, event & experience, public relations, direct marketing, personal selling, dan digital marketing secara simultan berpengaruh terhadap keputusan mendaftar siswa di SMK Telkom Sidoarjo.